Principal component analysis of body measurements based morphological structure of Madgyal sheep - YADAV, DINESH KUMAR; ARORA, REENA; JAIN, ANAND (The Indian Journal of Animal Sciences, 2016)
The present study describes the morphometric structure of extensively managed Madgyal sheep of Maharashtra and predicts body weight from their body biometry traits using principal component analysis (PCA). The data on body weight and 13 body measurements were recorded on 200 randomly selected sheep. Phenotypic correlation among body weight and biometric traits were positive and highly significant except some of ear length related combinations. The PCA of morphometric traits extracted two components with a total variance 67.8% explained. The first factor had high loadings for variables related to body size, whereas second factor was loaded in favour of body shape. PCA was able to define the morphological structure of Madgyal sheep and identified traits with greater variability. The principal component based regression models were more appropriate than the use of original correlated variables in predicting the body weight. The findings could be useful in designing management, selection and breeding programmes of the Madgyal sheep.